Running head: GSM consumption value scale development and validation of global system mobile (gsm) consumption value scale in Nigeria (2012)
The specific purpose of this study was the development and validation of Global System Mobile Consumption Value Scale (GSM-CVS) using Nigerian sample. To this end, 40 items were generated from literature and interviews with GSM users, items analysis through pilot study that involved 104 participants led to the dropping of 11 items that loaded below 30 thereby leaving 29 items for the main study. The scale yielded Alpha reliability coefficient of .84. Using accidental and purposive sampling techniques, a total of 763 people from both the northern and southern part of the country participated in the study. Principal Component Analysis (PCA) and Varimax with Kaiser Normalization rotation method yielded 6 factors with eighteen values greater than 1.00. The factors were found to have correlations with one another, while age differences were not found. The overall contribution of the factors was less than 10% with functional value having the greatest effect followed by health value while monetary, social, emotional and safety did not have significant effect on consumption value. In fall, it is established that this scale is a valid measure of GSM consumption value.